Les difficultés et les besoins de soutien des enseignants débutants en adaptation scolaire - Fanny Giguère; Joséphine Mukamurera
In Quebec, studies on the teacher induction do not enlighten the special situation of those working in the field of special education. Constituting a significant portion of the teaching staff (gouvernement du Québec, 2016) and working with vulnerable and exclusively troubled students, these teachers face relatively different challenges from those of their colleagues working in regular classes. Our goal is to describe and understand the challenges they face and their support needs. An existing database based on a multidimensional approach of teacher induction has been used for secondary analysis. Semi-structured interviews were also realized. The results reveal the diversity of the difficulties encountered and the plural nature of the support needs of beginning teachers in special education some of which are inherent to their particular working contexts.